An Analysis of Sellers’ Social Capital at Kota Teluk Kuantan Traditional Market - Andri Meiriki; Rika Ramadhanti (Ilomata International Journal of Social Science, 2020)
The present study was aimed at: (1) finding out and understanding the forms of social capital presenting among sellers at Kota Teluk Kuantan Traditional Market; (2) Analyzing the social capital within the interaction and transaction process among the sellers at Kota Teluk Kuantan Traditional Market. The present study was conducted at Kota Teluk Kuantan traditional market, Kuantan Singingi Regency, Riau. To this end, descriptive qualitative method was applied. This study revealed that: (1) Social capital established in Kota Teluk Kuantan traditional market comprised networks, social norms, trust from each market actors, (2) the trading culture makes the sellers adjust themselves to the relationship and social interactions that occur in the market. (3) The presence of social capital in the market reflects a significant role in promoting the sustainability of the traditional market in the midst of the continuous development of social and economic life in Teluk Kuantan.